Fire in the Water: Baptismal Aptness and Ecology in the Petrine Epistles - Schlesinger, Eugene R. (Journal of theological interpretation, 2013)
Despite some notable and vocal objections, the claim that Christians bear a responsibility toward the environment is now more or less a truism. In this article, I seek to strengthen, rather than prove, that commitment by an argument ex convenientia (from aptness). I analyze the Petrine epistles' imagery of water and fire. I make explicit the connections between these images and the sacrament of baptism as well as their connection to creation, redemption, and the eschatological consummation. By this analysis, I aim to forge reinforcing symbolic links between biblical interpretation, sacramental practice, and the created order, thereby solidifying and foregrounding Christian commitments to ecological engagement. My primary theological interlocutors are Karl Barth and Sergius Bulgakov, whom I consult to make sense of the imagery of water and fire, respectively. My treatment of Barth and Bulgakov allows me to use their respective theologies to supplement what I perceive as one another's weak points. This gives an ecology that is concretely rooted in the Christ event (from Barth), and which demands human participation and sacramentality (from Bulgakov).